Evaluation of Railway Switch Drive Operating Condition Using Control Current Features - Daunoras, J.; Gargasas, V.; Knyš, A. (Elektronika ir Elektrotechnika, 2010)
This paper presents the results on investigation of railway switch drive operating condition using control current features. The problem is formulated in introduction – now operator subjectively judges the state of the drive by a control current strength. A structural scheme and a description of drive control system are presented. The results of experiment at Lithuanian railways that represent switch drives of three different conditions (good, with progressing fault and faulty) are presented. The investigation of control current features was carried out and, as the result, the method that allows automatically and in real–time classify drives of different operating conditions is presented. Also the proposed structure of modernized centralization post and conclusions are given.